ANALISIS PERILAKU KONSUMEN TERHADAP KOPI TELAPEN PADA ERA NEW NORMAL DI BATUKLIANG UTARA KABUPATEN LOMBOK TENGAH - Nurul Aini; Syarif Husni; Muhamad Siddik (JURNAL AGRIMANSION, 2021)
This study aims to identify general characteristics, analyze consumer behavior, analyze consumer attitudes, analyze the purchase decision process. telapen coffee in the new normal era in North Batukliang District, Central Lombok Regency. This research uses a descriptive method. Determination of the research location is determined by purposive sampling technique. Determination of the number of consumer samples is determined by the Quota sampling technique of 30 respondents. The analytical tools used in this study are fishbein multi-attribute analysis and subjective normative analysis to measure consumer behavior and attitudes. Descriptive analysis to measure the characteristics and purchasing decision process of telapen coffee consumers. The results of this study indicate that telapen coffee consumers have the possibility to buy back telapen coffee products and have a favorable attitude towards telapen coffee products and feel satisfied with telapen coffee products. Based on the results of these studies should KVWT Kaki Rinjani should be. lower prices to increase coffee demand. telapen. must be able to maintain the attributes that can attract new customers and retain old customers.